The scale, scope, coverage, and capability of childbirth care. Issue 10056 (29th October 2016) - Campbell, Oona M R; Calvert, Clara; Testa, Adrienne; Strehlow, Matthew; Benova, Lenka; Keyes, Emily; Donnay, France; Macleod, David; Gabrysch, Sabine; Rong, Luo; Ronsmans, Carine; Sadruddin, Salim; et al.
Summary: All women should have access to high quality maternity services—but what do we know about the health care available to and used by women? With a focus on low-income and middle-income countries, we present data that policy makers and planners can use to evaluate whether maternal health services are functioning to meet needs of women nationally, and potentially subnationally. We describe configurations of intrapartum care systems, and focus in particular on where, and with whom, deliveries take place. The necessity of ascertaining actual facility capability and providers' skills is highlighted, as is the paucity of information on maternity waiting homes and transport as mechanisms to link women to care. Furthermore, we stress the importance of assessment of routine provision of care (not just emergency care), and contextualise this importance within geographic circumstances (eg, in sparsely-populated regions vs dense urban areas). Although no single model-of-care fits all contexts, we discuss implications of the models we observe, and consider changes that might improve services and accelerate response to future challenges. Areas that need attention include minimisation of overintervention while responding to the changing disease burden. Conceptualisation, systematic measurement, and effective tackling of coverage and configuration challenges to implement high quality, respectful maternal health-care services are key to ensure that every woman can give birth without risk to her life, or that of her baby.